Sri Lanka - Demographic Transition : Facing the Challenges of an Aging Population with Few Resources - World Bank (Washington, DC, 2013)
As a result of low fertility rates and high life expectancy, the current demographic trends in Sri Lanka include a declining share of children and increasing share of elderly, and (for now) an increasing working age population. Sri Lanka has a unique window of opportunity to take advantage of the high share of working age population to stimulate economic growth, but the other two emerging population issues spur questions on their own. In this context, the report discusses some of the economic implications of demographic transition in Sri Lanka, focusing on employment and productivity related issues on one side; and performance of cash transfer programs aiming to assist the poor and vulnerable groups on the other. This report quantifies Sri Lanka's demographic change by providing updated population projections and by applying National Transfers Accounts methodology documenting how the demographic change and aging contribute to life-cycle deficit and to Sri Lanka's employment and labor market. The challenges and opportunities associated with the upcoming demographic transition are highlighted, focusing on the functioning of the labor markets and the social safety net system. The report discusses different avenues that the country can take to make its labor market more efficient and inclusive, and offset some of the disadvantages faced by the poor and vulnerable households. The analysis in this report suggests that timely policy actions can enable Sri Lanka to effectively cope with its changing demographic structure.